Differences in metabolic profiles between the Burmese, the Maine Coon and the Birman cat - three breeds with varying risk for diabetes mellitus - Ström Holst, Bodil; Öhlund, Malin; Moazzami, Ali; Mullner, Elisabeth; Anderson, Fredrick (Swedish University of Agricultural Sciences, 2021)
Feline diabetes mellitus shares many features with type 2 diabetes in people, regarding clinical presentation, physiology, and pathology. A breed predisposition for type 2 diabetes has been identified, with the Burmese breed at a fivefold increased risk of developing the condition compared to other purebred cats. We aimed to characterize the serum metabolome in cats (n = 63) using nuclear magnetic resonance metabolomics, and to compare the metabolite pattern of Burmese cats with that of two cat breeds of medium or low risk of diabetes, the Maine coon (MCO) and Birman cat, respectively. Serum concentrations of adiponectin, insulin and insulin-like growth factor-1 were also measured (n = 94). Burmese cats had higher insulin and lower adiponectin concentrations than MCO cats. Twenty one metabolites were discriminative between breeds using a multivariate statistical approach and 15 remained significant after adjustment for body weight and body condition score. Burmese cats had higher plasma levels of 2-hydroxybutyrate relative to MCO and Birman cats and increased concentrations of 2-oxoisocaproic acid, and tyrosine, and lower concentrations of dimethylglycine relative to MCO cats. The metabolic profile of MCO cats was characterized by high concentrations of arginine, asparagine, methionine, succinic acid and low levels of acetylcarnitine while Birman cats had the highest creatinine and the lowest taurine plasma levels, compared with MCO and Burmese. The pattern of metabolites in Burmese cats is similar to that in people with insulin resistance. In conclusion, the metabolic profile differed between healthy cats of three breeds. Detection of an abnormal metabolome might identify cats at risk of developing diabetes.
The study was approved by the ethics committee on animal experiments in Uppsala, reference number C 299/12 and C 12/15, and by the Swedish Board of Agriculture, reference number 31-11654/12.

Results from analysis of blood samples from healthy cats of three breeds: Burmese, Birman and Maine coon, are included. A clinical examination was performed on the cats and information noted. Hormones were analysed in serum using immunological methods. Lipoproteins were analysed using HPLC (high performance liquid chromatography) and metabolomics using NMR (nuclear magnetic resonance) spectroscopy.

Studien beskriver metabolomet hos tre kattraser med olika hög risk att utveckla diabetes mellitus. Se vidare engelsk sammanfattning.
Studien godkändes av Uppsala Djurförsöksetiska nämnd, diarienummer C 299/12 och C 12/15, samt av Jordbruksverket, diarienummer 31-11654/12.

Blodprov har tagits från friska katter av tre raser; burma, birma och maine coon. Katterna har undersökts kliniskt och uppgifter om dem har noterats. Serum har analyserats avseende hormoner med immunologiska metoder, lipoproteiner har analyserats med HPLC (high performance liquid chromatography) och metabolomics studerades med NMR-spektroskopi (nuclear magnetic resonance spectroscopy).
Skillnad i metabola profiler mellan katter av raserna burma, maine coon och birma - tre raser med olika hög risk att utveckla diabetes mellitus
Keywords: Diabetes Mellitus; Diabetes; Human health and safety; Människors hälsa och säkerhet; cat; katt; diabetes mellitus; diabetes mellitus; metabolomics; metabolomik; Plants and animals; Växter och djur; Clinical Science; Klinisk vetenskap